THE ABILITY TO CLEAN THE TRACK STRUCTURE WITH PULSATING AND CAVITATING WATER JETS AT MOTION OF ROLLING STOCK - Zhulai, Yu. O.; Dzoz, N. O.; Zadontsev, V. O.; Burylov, S. V.; Novikov, V. F. (Science and Transport Progress, 2005)
The paper gives the results of studies on hydrodynamic cleaning surfaces with pulsating and cavitating sprays, obtained in a device including local flow resistance — Venturi tube of special geometry. The use of the above technologies to clean the rail track should decrease considerably the expenses as compared to the current cleaning technology by blasting sand under locomotive leading wheels.